Peran Mediasi Kemampuan Operasional pada Pengaruh Kolaborasi Rantai Pasok Terhadap Kinerja Operasional Usaha Laundry di Tangerang Selatan - Ratna Darasih; Arlen Verta Ramadhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of supply chain collaboration on operational performance in laundry business in South Tangerang, as well as the mediating role of operational capabilities in this relationship. Supply chain collaboration has been recognized as an important approach to improving company operational performance. This study focuses on the laundry service industry, which is an essential part of the modern economy, especially in large cities. The research was conducted using a survey method with a Likert scale to collect data from laundry business owners and managers.This study employs a Hypothesis Testing approach and a Cross-Sectional strategy to test the formulated hypotheses, utilizing Structural Equation Modeling (SEM) and AMOS software. All hypotheses are supported by valid and reliable data. The findings of this study provide significant contributions to the understanding of supply chain and operational management, as well as offering practical insights for laundry business managers to enhance their operational performance.This research uses a